TEACHERS' EFFORTS IN IMPROVING STUDENTS' EMOTIONAL AND SPIRITUAL INTELLIGENCE IN PRANCAK II BANGKALAN ELEMENTARY SCHOOL - Auliya Niswatul Farichah; Ahmad Walid Hujairi; Fitri Wijayanti; Titania Athaya Shafa Almirah; Conny Dian Sumadi (maktab: Jurnal Pendidikan dan Teknologi, 2022)
Emotional and spiritual intelligence are two types of intelligence that are very important to be honed so that a person can achieve success in life, in addition to intellectual intelligence. The purpose of this study was to determine the role and efforts of grade 2 teachers at SDN Prancak II Bangkalan in improving students' emotional and spiritual intelligence. The research method used in this study used a qualitative approach with interview data collection techniques and observations to teachers and students in grade 2 UPTD SDN Prancak II Bangkalan. The data analysis technique in this study uses the analytical technique of Milles and Huberman which consists of three flow of activities that occur simultaneously, namely: data reduction, data presentation, conclusion drawing/verification. Based on the results of research that has been done, teachers have a significant role in increasing the emotional and spiritual intelligence of students. Some of the efforts that have been made include teaching caring attitudes, getting used to behavior based on the Pancasila precepts, providing examples to students, instilling the value of honesty, reminding and familiarizing students to obey religious teachings, providing advice and solutions to students, conducting discussions with parents/guardians of students. / other teacher colleagues, as well as evaluating learning activities. Based on the results of observations and interviews conducted, these efforts have a positive impact in increasing students' emotional and spiritual intelligence.